Management of Badminton Sports Achievement Development at PB Arista Semarang Club - Sintya Defini Nilamsari; Ibnu Fatkhu Fatkhu Royana; Setiyawan Setiyawan (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The purpose of this study is to analyze the management of badminton sport achievement coaching at the PB Arista Semarang club. Materials and Methods. Qualitative methodologies were implemented in this investigation. Interviews, documentation, and observation are employed as data collection methods. The data analysis or research stage is comprised of four stages: data collection, data reduction, data presentation, and conclusion drawing. Results. The first aspect of this investigation is that athletes at PB Arista Semarang are classified into four categories: basic, middle, main, and achievement. Secondly, all coaches are athletes and possess Badminton World Federation (BWF) certificates. Third, the management is comprised of coaches and proprietors who collaborate effectively and consistently. Conclusion. In particular, the administration of achievement coaching has been implemented with a relatively effective strategy, despite the presence of some challenges from both athletes and their parents.